Rabindranath Tagore’s Religious Ideology: A Study of Nationalistic Liberalism in Gora - Dr. Sumit Sharma (The Creative Launcher, 2017)
Being an emblem of faith and conviction and one of the earliest institutions of mankind, Religion as a universal social phenomenon is the most powerful means of controlling society. Individual perception of respective religion makes it an ‘institutional religion’ that further becomes a mode of sociological tool rather than being a spiritual one leading to debates and deliberations. Keeping in cue with the face of continuing debate about the concept of religion, the aim of the present research lies in the study and documentation of the concept of religion and how the institutional religion plays a key role in Tagore’s Gora. The study is basically explanatory and descriptive in nature. Through Gora, Tagore in his work enunciates his developing philosophy about Hinduism. The research highlights how the notion of dialectics and its visibility in the novel evolves a kind of ‘universalism’ that has eventually become Tagore’s legacy.